2014
DOI: 10.3389/fpsyg.2014.01376
|View full text |Cite
|
Sign up to set email alerts
|

Color-discrimination threshold determination using pseudoisochromatic test plates

Abstract: We produced a set of pseudoisochromatic plates for determining individual color-difference thresholds to assess test performance and test properties, and analyzed the results. We report a high test validity and classification ability for the deficiency type and severity level [comparable to that of the fourth edition of the Hardy–Rand–Rittler (HRR) test]. We discuss changes of the acceptable chromatic shifts from the protan and deutan confusion lines along the CIE xy diagram, and the high correlation of indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Existing diagnostic tests for CVD are typically based on a criterion score of raw protan and deutan thresholds between individuals (Barbur & Rodriguez-Carmona, 2015 ; Jurasevska et al, 2014 ; Mollon et al, 1991 ; Rabin et al, 2011 ). We found this to be a suboptimal metric on which to base classification for young children, because the raw thresholds along a given confusion axes do not account for individual differences in non-visual factors such as attention, motivation and engagement that influence task performance (Bosten et al, 2017 ; Dain & Ling, 2009 ; Ling & Dain, 2018 ; see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Existing diagnostic tests for CVD are typically based on a criterion score of raw protan and deutan thresholds between individuals (Barbur & Rodriguez-Carmona, 2015 ; Jurasevska et al, 2014 ; Mollon et al, 1991 ; Rabin et al, 2011 ). We found this to be a suboptimal metric on which to base classification for young children, because the raw thresholds along a given confusion axes do not account for individual differences in non-visual factors such as attention, motivation and engagement that influence task performance (Bosten et al, 2017 ; Dain & Ling, 2009 ; Ling & Dain, 2018 ; see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a correlation between the severity of color vision deficiency and dE units has been reported [39]. A low-severity defect has a dE of around 22 units, a mild-severity defect has a dE of around 40 units, and a high-severity defect dE is around 60 units [41].…”
Section: Dive Color Testmentioning
confidence: 99%
“…Souza et al [10] used the Cambridge Color Test (CCT) to investigate the influence on color discrimination thresholds due to the number of luminance levels present in the luminance noise. Jurasevska et al [11] reported the classification ability for the deficiency type and severity level of human eyes. Madani et al [12] proposed a technique to recognize the traffic sign based on its border color, shape, and pictogram information.…”
Section: Current Color Discrimination Systemmentioning
confidence: 99%